Edukacja na rzecz zwierząt i ich praw. Uwagi w kontekście dyskursu o przemocy wobec zwierząt - Helios, Joanna (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The purpose of this article is to present the issues of violence against animals. This text is educational in nature. Sometime in our society violence against animals is often marginalized. Humanitarianism and animal welfare are pushed into the background. It is therefore worth considering the causes of animal cruelty.